Anti-Invariant Lorentzian Submersions From Lorentzian Concircular Structure Manifolds - Siddiqi, M. Danish; Khan, Meraj A.; Ishan, Amira A.; Chaubey, S. K. (Frontiers in Physics, 2022)
This research article attempts to investigate anti-invariant Lorentzian submersions and the Lagrangian Lorentzian submersions (LLS) from the Lorentzian concircular structure [in short (LCS)n] manifolds onto semi-Riemannian manifolds with relevant non-trivial examples. It is shown that the horizontal distributions of such submersions are not integrable and their fibers are not totally geodesic. As a result, they can not be totally geodesic maps. Anti-invariant and Lagrangian submersions are also explored for their harmonicity. We illustrate that if the Reeb vector field is horizontal, the anti-invariant and LLS can not be harmonic.